Search for new physics in events with photons, jets, and missing transverse energy in $pp$ collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2197 authors) (2013)
A search for physics beyond the standard model involving events with one or more photons, jets, and missing transverse energy has been performed by the CMS experiment. The data sample corresponds to an integrated luminosity of 4.93 fb(−1) of proton-proton collisions at TeV, produced at the Large Hadron Collider. No excess of events with large missing transverse energy is observed beyond expectations from standard model processes, and upper limits on the signal production cross sections for new physics processes are set at the 95% confidence level. The results of this search are interpreted in the context of three models of new physics: a general model of gauge-mediated supersymmetry breaking, Simplified Models, and a theory involving universal extra dimensions. In the absence of evidence for new physics, exclusion regions are derived in the parameter spaces of the respective models.